Využití fuzzy logiky pro hodnocení dodavatelských rizik - Šidák, Matěj (Vysoké učení technické v Brně. Ústav soudního inženýrství, 2016)
Tato diplomová práce se věnuje hodnocení hlavních dodavatelů společnosti MERTASTAV s.r.o. a stanovení jejich míry rizika spolupráce. Cílem práce je navrhnout a vytvořit model pro efektivnější hodnocení dodavatelů. Při tvorbě modelu je využíváno principů fuzzy logiky a výsledný model je vyhotoven v prostředí programu MS Excel a MATLAB. Výstupem je pak nástroj přehledný a snadno ovladatelný, který urychlí a zkvalitní výběr dodavatele pro společnost.

This thesis is focused on the evaluation of the main suppliers of company MERTASTAV Ltd. and deals with the determination their risk level of cooperation. The aims of this thesis are design and create the model for effective evaluation of suppliers. During the creation of a mentioned model is used principles of fuzzy logics and the final model is processed in MS Excel and MATLAB. The result of this thesis is the clear instrument which is easy to use and also accelerates and improves selection of suppliers for the company.
The Use of Fuzzy Logic for the Evaluation of Supply Risk
Keywords: dodavatel; Excel; MATLAB; fuzzy logika; riziko; společnost; hodnocení.; supplier; Excel; MATLAB; fuzzy logic; risk; company; evaluation.